Effect of teaching motivational interviewing via communication coaching on clinician and patient satisfaction in primary care and pediatric obesity-focused offices. Issue 2 (February 2016) - Pollak, Kathryn I.; Nagy, Paul; Bigger, John; Bilheimer, Alicia; Lyna, Pauline; Gao, Xiaomei; Lancaster, Michael; Watkins, R. Chip; Johnson, Fred; Batish, Sanjay; Skelton, Joseph A.; Armstrong, Sarah
Highlights: Clinic staff can learn MI techniques via a coaching model. Learning as a team improves perceived team cohesion. Learning MI improves perceived burnout. Learning MI can improve patient satisfaction. Abstract: Objective: Studies indicate needed improvement in clinician communication and patient satisfaction. Motivational interviewing (MI) helps promote patient behavior change and improves satisfaction. In this pilot study, we tested a coaching intervention to teach MI to all clinic staff to improve clinician and patient satisfaction. Methods: We included four clinics ( n  = 29 staff members). In the intervention clinics (one primary care and one pediatric obesity-focused), we trained all clinic staff in MI through meetings as a group seven times, directly observing clinicians in practice 4–10 times, and providing real-time feedback on MI techniques. In all clinics, we assessed patient satisfaction via anonymous surveys and also assessed clinician burnout and self-rated MI skills. Results: Clinicians in the intervention clinics reported improvements in burnout scores, self-rated MI skills, and perceived cohesion whereas clinicians in the control clinic reported worse scores. Patient satisfaction improved in the intervention clinics more than in the control clinics. Conclusion: This is the first study to find some benefit of training an entire clinic staff in MI via a coaching model. Practice implications: It might help to train staff in MI to improve clinician satisfaction, team cohesion, perceived skills, and patient satisfaction.